Peer educator as a method to increasing the knowledge and attitude of HIV/AIDS prevention among nursing students in Samarinda (Berita Kedokteran Masyarakat (BKM), 2016)
PurposeThe purpose of this paper was to analyze the effect of health education through peer educator to increase of knowledge and attitude in HIV/AIDS prevention of nursing students in Samarinda.MethodA quasi experiment study was conducted involving 65 subject of the experiment group and control group. Data analysis used statistical paired t-test to identify difference in the two groups and independent t-test to compare knowledge and attitude of each group.ResultsThe study found that there was a significant statistic difference of  p < 0,05 in both of the groups. A significant increasing on knowledge and attitude average value in treatment group with peer educator method than the control group with a modules.ConclusionThis paper contributes to our understanding effectiveness of health education through peer educator increased knowledge and attitude of the HIV/AIDS prevention among  nursing students in Samarinda. It is expected that other universities can use this peer educator method to form groups of student mediators in conducting prevention activities of HIV / AIDS.